If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7p + 6 = 97 Reorder the terms: 6 + 7p = 97 Solving 6 + 7p = 97 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 7p = 97 + -6 Combine like terms: 6 + -6 = 0 0 + 7p = 97 + -6 7p = 97 + -6 Combine like terms: 97 + -6 = 91 7p = 91 Divide each side by '7'. p = 13 Simplifying p = 13
| 2x(7-3)+3(7-4)=16 | | 10+3D=55 | | 3000+36x=7000 | | p/27=4/9 | | 50p^2-18=0 | | 29x-11=7 | | 6(3s+1)=114 | | 9=8p | | 7(2l+9)=77 | | -28+5x-2x=3x | | 75a^2-3=0 | | -4(3-2x)=-20 | | -6r+3+4r=-29 | | sinx=-5/3 | | -n^2+3n+18=0 | | 3a-30=32 | | -2p^2-4p+16=0 | | 14=6(3-3x) | | 5(a-5)=15 | | 4h+7=15 | | u^2-10u+51=0 | | 5x-30=3x+20 | | 3(6x-2)=30 | | u^2+10u+51=0 | | -4(2t+8)=-56 | | 17+4.5x=13+5.75x | | 8t(7.5-2t)=h | | 6m^2-36=-30m | | -1c+4d=16 | | f(z)=z^2-(3+i) | | (q-9)*6=60 | | 5n^2=-16-42n |